Investment in rural infrasturcture: Critical for commercialization in Bangladesh - Ahmed, Raisuddin (International Food Policy Research Institute, 1994)
This chapter focuses on the role of rural infrastructure development on the pace of commercialization and the effects of such development on various income classes, especially for food-insecure poor, in the rural economy. Public expenditure and institutional policies for development of rural infrastructure are also considered. Although evidence is mostly drawn from Bangladesh, an effort is made to draw upon experiences elsewhere.